De rol van tijdelijk gebruik in de stedelijke (her)ontwikkeling: Brusselse voorbeelden - Aurelie de Smet (Brussels Studies, 2013)
As the realisation of urban projects is most often preceded by a long planning stage, urban (re)development areas frequently appear to uselessly lie in wait during certain periods of time. This can however have a negative impact on their environment. Moreover the presence of “useless space” is almost unacceptable, taking into account the strong demand for open and public spaces. This article describes how the current study ’The role of temporary use of waiting spaces in urban (re)development’ examines if temporary use of these areas could contribute to a more contemporary, flexible and spontaneous approach to urban development. More specifically 10 case studies are described in which the present situation and the existing opportunities for temporary use in the concrete context of the Brussels Capital Region have been explored. The objective is to put the possible role of temporary use in the urban planning of the Region on the agenda. In this way, the present contribution joins other current initiatives, such as the organisation of the symposium “Tijdelijke Publieke Ruimte Tussen Flexibiliteit en Planning” and the master class on “De Uitdaging van Tijdelijke Publieke Ruimtes” of the ]pyblik[ platform in September 2013.